1995
DOI: 10.1002/mrm.1910330613
|View full text |Cite
|
Sign up to set email alerts
|

NMR Relaxometric Investigation on Human Methemoglobin and Fluoromethemoglobin. An Improved Quantitative in Vitro Assay of Human Methemoglobin

Abstract: Longitudinal water proton relaxation rates of methemoglobin solutions show a strong dependence on temperature and pH. The increase of the relaxation rates with temperature is associated with shortened exchange lifetime of the coordinated water molecule. An accurate measurement of the relaxation rate of methemoglobin solutions thus requires careful control of the experimental temperature. This observation prompted the authors to look for an improved version of the relaxometric in vitro determination of methemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…However, the 1 H relaxation rates shown in Figs. 1 and 2 are much higher than those reported for other ferric hemoproteins [19,28,29], and cannot be accounted for by a simple diffusion-controlled mechanism (i.e., water molecules diffusing in proximity of the paramagnetic center [12,24]). Rather, a second-sphere contribution (i.e., water molecules bound to the protein in close proximity of the ferric heme and mobile protons on the surface of the protein) appears a reasonable explanation for the observed high relaxation rates.…”
Section: Characterization Of the Fe(iii)heme-hsa Complexmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the 1 H relaxation rates shown in Figs. 1 and 2 are much higher than those reported for other ferric hemoproteins [19,28,29], and cannot be accounted for by a simple diffusion-controlled mechanism (i.e., water molecules diffusing in proximity of the paramagnetic center [12,24]). Rather, a second-sphere contribution (i.e., water molecules bound to the protein in close proximity of the ferric heme and mobile protons on the surface of the protein) appears a reasonable explanation for the observed high relaxation rates.…”
Section: Characterization Of the Fe(iii)heme-hsa Complexmentioning
confidence: 89%
“…With both ligands, the paramagnetic contribution to the overall solvent relaxation rate tends to zero. On the other hand, fluoride binding is known to increase the relaxivity of hemoproteins [19,28,31,32], since the incoming fluoride ion brings a fast-exchanging hydrogen-bonded water molecule in close proximity to the paramagnetic center. Accordingly, fluoride binding yields a slight increase of the water proton relaxation rate, suggesting that the overall hydration sphere is not too different from that of the parent Fe(III)heme-HSA.…”
Section: Characterization Of the Fe(iii)heme-hsa Complexmentioning
confidence: 99%
“…Relaxivity in heme-proteins is usually due to second-sphere contributions, i.e., water molecules bound to the protein in the close proximity of a paramagnetic metal center and able to exchange with the bulk water [35][36][37]. Heme-HSA shows a considerably high r 1 value (approximately 25 s -1 mM -1 ), compared with other heme-proteins such as hemoglobin and myoglobin [11,19,32,[48][49][50][51]. Nuclear magnetic relaxation dispersion studies of heme-HSA revealed a strong paramagnetic contribution due to a cluster of water molecules buried near the heme that may be employed to follow a number of events including conformational transitions [16].…”
Section: Discussionmentioning
confidence: 99%
“…To gain more insight into the understanding of the ligand recognition processes operating in heme proteins, we investigated the fluoride and formate binding mode to A. limacina Mb, horse (Caballus caballus) Mb, sperm whale (Physeter catodon) Mb, loggerhead sea turtle (Caretta caretta) Mb, and human hemoglobin (Hb) by x-ray crystallography and 'H-NMR relaxometric techniques. The presence of a water molecule close to HisE7 and hydrogen bonded to the heme coordinated fluoride anion (Deatherage et al, 1976;Fermi and Perutz, 1977;Perutz, 1979), which was just supposed to be present based on measurements in solution (Fabry and Eisenstadt, 1974;Koenig et al, 1981;Oakes, 1986;Aime et al, 1993Aime et al, , 1995, has now been definitely assessed. On the other hand, in A. limacina Mb, bearing Val(63)E7, the fluoride anion is hydrogen bonded only to the Arg(66)E1O side chain (Bolognesi et al, 1990;Conti et al, 1993), and there are no water molecules in closest proximity to the heme-iron bound ligand.…”
Section: Introductionmentioning
confidence: 99%